Hamstring exercises for track and field athletes: injury and exercise biomechanics, and possible implications for exercise selection and primary prevention. Issue 12 (9th June 2012) - Malliaropoulos, Nikos; Mendiguchia, Jurdan; Pehlivanidis, Hercules; Papadopoulou, Sofia; Valle, Xavier; Malliaras, Peter; Maffulli, Nicola
Abstract : Hamstring strain injuries are the most prevalent muscle injuries in track and field (TF). These injuries often cause prolonged symptoms and a high risk of re-injury. Strengthening of the hamstring muscles has been recommended for injury prevention. The authors review the possible role of eccentric training in TF hamstring injury prevention and introduce exercise classification criteria to guide clinicians in designing strengthening programmes adapted to TF. The principles exposed may serve as a foundation for future development and application of new eccentric programmes to decrease the high incidence of this type of injury in other sports.